Transition to Surgical Practice: The Early Years - Paquette, Ian M. (Clinics in Colon and Rectal Surgery, 2019)
The transition from years of surgical training to independent surgical practice is a time to enjoy the well-earned achievement of completion of training. The early years of clinical practice bring about many challenges to the young surgeon. These include transitioning to a more independent role in the operating room, running an office and understanding the business aspects of medicine, building clinical networks to sustain a clinical practice, and building a professional and academic reputation. This article will discuss aspects that are unique to the early career surgeon. Where possible, I will use the available literature to augment the discussion, whereas, in other areas, I will offer my thoughts from personal experience on the topic.
Keywords: early career; transition; surgical practice